Effects of land-use change after tsetse control on biological diversity: The case of northwestern Zimbabwe - Gardiner, A.J.; Reid, Robin S. (OAU/STRC, 1999)
It has been hypothesized that the presence of the tsetse fly has protected the biological diversity of the African continent by preventing over-use of ecosystems by people and their livestock. Our objective was to evaluate how changes in land-use, a likely impact of tsetse control, affect selected aspects of biological diversity in three vegetation types at two sites in northwestern Zimbabwe (Busi Valley, Kanyati). This is part of a continent-wide project designed to look at these issues. The taxonomic groups used were large mammals, small mammals, birds, butterflies, dung beetles, herbaceous plants and woody plants. The structure of the vegetation was also analysed. In both Busi Valley and Kanyati, species numbers and abundances were compared in protected areas (used principally by indigenous megaherbivores) to nearby communal farmlands in the wet and dry seasons of 1995 and 1996. These sites were selected to simulate possible ecosystem states before and after tsetse control. Additional information about the effect of land-use change on dung beetles is added from other studies conducted by the first author in western (Hwange and Matopos) and central (wedza) Zimbabwe. A new sampling method was devised to study multiple taxonomic groups on the same transect at a landscape scale of resolution.